Observed warming trend in sea surface temperature at tropical cyclone genesis. Issue 2 (28th January 2017) - Defforge, Cécile L.; Merlis, Timothy M.
Abstract: Tropical cyclone (TC) activity is influenced by environmental factors, and it is expected to respond to anthropogenic climate change. However, there is observational uncertainty in historical changes in TC activity, and attributing observed TC changes to anthropogenic forcing is challenging in the presence of internal climate variability. The sea surface temperature (SST) is a well‐observed environmental factor that affects TC intensity and rainfall. Here we show that the SST at the time of TC genesis has a significant warming trend over the three decades of the satellite era. Though TCs are extreme events, the warming trend at TC genesis is comparable to the trend in SST during other tropical deep convection events and the trend in SST in the TC main development regions throughout the TC season. This newly documented, observed signature of climate change on TC activity is also present in high‐resolution global atmospheric model simulations that explicitly simulate TCs. Key Points: SST at TC genesis has significantly increased over the past three decades, a new fingerprint of anthropogenic climate change on TC activity The observed warming trend in SST at TC genesis is primarily from the temporal changes of the basins' SST The significant warming trend is also found in TC tracks of TC‐permitting GCM